La articulación entre la docencia, la extensión y la investigación, una realidad posible en la Escuela de Nutrición y Dietética de la Universidad de Antioquia : sistematización de una experiencia (2016)
ABSTRACT: The Escuela de Nutrición y Dietética [School of Nutrition and Dietetics] at the University of AntioquiaColombia, executed during 2013-2014 the “Information and Communication Strategy on Nutrition Food Labelling to Contribute to the Prevention of Chronic Diseases”, funded by Ministry of Health of Medellin. The execution and evaluation of this strategy through community-institutional relations allowed systemization of the process from the perspective of 26 participating students. Objective: To systematize the experience of the participating students in the execution of the strategy in order to understand their learning acquired during the process. Materials and Methods: A qualitative study was conducted using the methodology of retrospective experience systematization, the guiding question was “What lessons were learned by the students, as a result of their participation in the implementation of the Strategy?” The categorical system was constructed from data collected by focus groups, a semi-structured interview, and Facebook®. Results: Three initial categories were analyzed: motivation, learning. and difficulties, and a new category emerged which was labeled ‘conception of education’. Conclusions: Involving students in community-institutional relation processes generates meaningful, relevant and contextual learning, encourages the development of critical, reflective and purposeful skills about their work, and permits the understanding of education as a two-way, reflective process.